(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
Carlo Alberto Pisani Dossi (1849-1910) was a leading figure of the late nineteenth century thanks to his eclecticism, his political role and his interest in archaeology. During his diplomatic activity he acquired many ancient finds and after retiring from political life, he devoted himself entirely to archaeology, launching several excavations. Among the various types of finds that make up the Pisani Dossi Collection are twentyseven terracottas statuettes depicting various animals, eighteen of which are horse-shaped. The lack of the context of discovery doesn’t help to give a complete analysis on the function of these statuettes, which, however, for similar decorative elements refer to the geographic area of the Boethia. The differences are considerable with the indigenous world in Magna Grecia regarding decoration, while a similar function is conceivable within a sacred context. The importance of this Collection is the intent to rebuild the ancient everyday life with the exhibits less flashy.